2014
DOI: 10.5617/jmi.v1i2.875
|View full text |Cite
|
Sign up to set email alerts
|

Working with or next to each other? Boundary crossing in the field of information visualisation

Abstract: Due to the need to present information in a fast and attractive way, organizations are eager to use information visualisations. This study explores the collision between the different experts involved in the production of these visualisations using the model of trading zones supplemented with the learning mechanisms found in the boundary crossing literature. Results show that that there is not one single good solution to effective interdisciplinary cooperation in the field of information visualisation. Rather,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…That key finding underscores the challenge of uniting disparate groups around a boundary object (Smit et al, 2014;Star & Griesemer, 1989). For example, Lewis and Usher (2014) found that limited organizational support and a lack of sustained and enduring exchanges made it hard for Hacks/Hackers groups to maintain momentum.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…That key finding underscores the challenge of uniting disparate groups around a boundary object (Smit et al, 2014;Star & Griesemer, 1989). For example, Lewis and Usher (2014) found that limited organizational support and a lack of sustained and enduring exchanges made it hard for Hacks/Hackers groups to maintain momentum.…”
Section: Discussionmentioning
confidence: 97%
“…Not all collaboration is useful, though. Indeed, some trading zones may prove unproductive as more time is spent negotiating meanings and frictions than advancing ideas (Smit et al, 2014).…”
Section: Sociotechnical Collaboration In Journalismmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, taking the clustering of accounts not as a definitive classification of communicative user behavior and political stances, but leaving space for interpretative ambiguities and doubt in this encoding and analytical process constituted an area of conflict. Frictions in the collaboration derived in part from the separation of our analytical work and the journalists' investigative process (data analysis and content production did not go hand in hand, as discussed by Smit et al, 2014). The fact that the project started off with certain reporting hypotheses-i.e., the idea that This collection of tweets was not limited to retweets, but we broadened our sampling scope and included all kinds of tweets containing media references (hyperlinks).…”
Section: What Do Network Mean? Trouble Interpreting and Reporting On ...mentioning
confidence: 99%
“…The press no longer has the exclusivity of the news, but other media take center stage, which is why some authors are beginning to study the importance of combining data visualization with news with interaction, to attract more audiences (Freixa et al, 2021). Following this idea, these techniques have the ability to attract readers by integrating large amounts of data into the news (Schroeder, 2004;Smit et al, 2014), which makes it possible to understand complex news topics (Bakker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%